2019
DOI: 10.1002/cam4.2691
|View full text |Cite
|
Sign up to set email alerts
|

Selected psychological aspects and medication adherence in oncological patients

Abstract: Objective: The aim of this study was to analyze the relationships between selected psychological features and adherence to therapy in oncological patients. Methods: The study included 102 patients of oncological clinics, 66.67% of whom were female. The average (SD) age of the study subjects was 49.15 ± 18.16 years old. The following tools were used: Morisky Medication Adherence Questionnaire (MAQ-4), Multidimensional Health Locus of Control, Coping Inventory for Stressful Situations,Personal Values Inventory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This finding is consistent with the results of a study conducted in a group of oncological patients, which confirmed a significant correlation between the level of medication adherence and the use of avoidance-oriented strategies of coping with stress, including the willingness to engage in social relationships [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the results of a study conducted in a group of oncological patients, which confirmed a significant correlation between the level of medication adherence and the use of avoidance-oriented strategies of coping with stress, including the willingness to engage in social relationships [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Studies exploring the relationships between coping strategies and medication adherence are not extensive. For instance, such a study was conducted in a group of oncological patients [ 16 ]. However, no reports analysing this relationship in RA patients have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, education level was significantly associated with the participants’ beliefs about medication which in turn was significantly associated with adherence level. Focus on modifiable predictors including factors related to behavioral aspects [ 35 ], costs [ 36 ], and therapy regimens complexity [ 37 ] has recently increased. Consistent with earlier research findings [ 25 , 27 , 38 , 39 ], patients’ beliefs about diabetes medications was significantly associated with medication adherence in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that adherent versus non-adherent patients used more active coping strategies (i.e., seeking information about illness and therapy), and also reported more diverting (i.e., distracting with something pleasant) and self-encouraging (i.e., seeking success, indulge oneself) behavior [ 21 ]. The results of a study conducted in a group of oncological patients confirmed a significant correlation between the level of medication adherence and the use of avoidance-oriented strategies of coping with stress, including willingness to engage in social relationships [ 22 ]. Additionally, a study in a group of patients with rheumatological diseases showed that a low level of internal health locus of control increased the likelihood of medication adherence [ 23 ].…”
Section: Introductionmentioning
confidence: 95%